Penanaman Nilai - Nilai Multikultural Dalam Pembelajaran Sejarah Di MA Tahfizhil Quran - Fitri Ainun Nisa; Ervina Fauziah Harahap; Putri Alawiyah; Ainun Zariah; Putri Elsanai Manao SM (BEST Journal (Biology Education, Sains and Technology), 2022)
The purpose of the study was to find out the multicultural values instilled in history learning in the Madrasah Aliyah Tahfizhil Qur'an, know the implementation of multicultural values in the Madrasah Aliyah Tahfizhil Qur'an, and know what obstacles were faced in instilling multicultural values in the Madrasah Aliyah Tahfizhil Qur'an. This research is a type of qualitative research. Data collection techniques are carried out by observation, interviews and documentation. The technique of checking the validity of the data uses triangulation techniques and sources. The data analysis used is an Interactive analysis model. Based on the results of the study, it was revealed that the cultivation of multicultural values in history learning taught in the Madrasah Aliyah Tahfizhil Qur'an has been carried out well. The cultivation of multicultural values in history learning in Madrasah Aliyah Tahfizhil Qur'an is not only taught in the classroom, but also through out-of-class learning. The curriculum is an inhibiting factor in instilling multicultural values in the Madrasah Aliyah Tahfizhil Qur'an Rembang, and out-of-class learning is a driving factor in the cultivation of multicultural values.